Principal’s Academic Supervision and Teacher’s Performance - Wardana, Satria Wisnu; Susanto, Edy; Nipriansyah, Nipriansyah (PPSDP International Journal of Education, 2023)
The purpose of this study is to identify the principal’s academic supervision at MTs Amal Bakti Prabumulih, how teachers’ performance at MTs Amal Bakti Prabumulih is, and how the principal’s academic supervision influences teacher’s performance at MTs Amal Bakti Prabumulih. This is a descriptive quantitative study. The sampling strategy used in this study is saturation sampling, and the sample size is 16 persons. The dissemination of surveys and documentation approaches were utilized to obtain data. In addition, data analysis procedures such as descriptive analysis in the form of percentages and inferential analysis employing analytical precondition tests and hypothesis testing were used (t-test). The findings revealed that: (1) the principal’s academic supervision was quite good, (2) teacher’s performance was said to be good, and (3) there was a significant effect of the principal’s academic supervision on the performance of teachers at MTs Amal Bakti Prabumulih, where the probability value obtained was less than the significant level.